An Education Intervention to Raise Awareness Reduces Self-reported Opioid Overprescribing by Plastic Surgery Residents. Issue 6 (December 2022) - Skladman, Rachel; Keane, Grace C.; Grant, David; Mackinnon, Susan E.
Abstract : Purpose: The aim of this study was to understand how opioid prescribing practices of plastic surgery residents changed after instituting opioid prescribing education (OPE) interventions. Methods: Plastic surgery residents at a single academic institution completed a survey (fall 2017) assessing opioid prescribing following 8 common procedures. The Division then completed 3 multidisciplinary OPE interventions over 2.5 years, which provided passive learning to raise awareness without top-down prescribing guidelines. Residents were resurveyed at 2 time points after the interventions (fall 2018 and spring 2020). The primary outcome measure was self-reported morphine milligram equivalents prescribed. Results: Survey response rates were 84% to 100%. Preintervention opioid prescriptions were characterized by high variability and absolute doses for all procedures. We observed statistically significant decreases in prescribed doses for most procedures at 9 months post intervention and further decreases at 2.5 years. In the most recently surveyed cohort, only 3 of 16 residents (18.8%) had OPE before residency, whereas 12 of 16 residents (75.0%) participated in OPE during residency. Eighty-eight percent of respondents "always" (8/16, 50%) or "usually" (6/16, 38%) considered the opioid epidemic when prescribing opioids, suggesting an improved prescribing culture. Barriers to better prescribing included duplicate prescriptions/accessing state-run prescription drug monitoring programs (75.0%), remote prescribing (75%), providing refills (56%), and prescribing opioids for patients on chronic opioid therapy (56%). Conclusion: This prospective cohort study demonstrates that a simple multidisciplinary, didactic OPE intervention that aimed to increase residents' awareness has the potential to reduce self-reported opioid prescribing and sustain prescribing practices over many years. We identify persistent barriers facing our resident prescribers today, enabling more opioid educational interventions in the future.